Evaluation of Tsunami Disasters Caused by the 1923 Great Kanto Earthquake - Kaneko, Hiroyuki (Journal of disaster research, 2023)
The 1923 Great Kanto Earthquake is one of the earthquakes that have occurred multiple times in the past as part of the Sagami Trough earthquakes. These earthquakes, which occurred at the plate boundary, occurred in 1495 (Meio Earthquake), 1703 (Genroku Earthquake), and again in 1923, causing significant damage to various areas in Kanto, including Tokyo and Yokohama, and it came to be known as the Great Kanto Earthquake. The Sagami Trough earthquakes have consistently brought strong tsunami disasters to various areas in Kanto, extending from the Sagami Bay coast to the Boso Peninsula, and residents along the coast were highly aware of the risk of tsunamis occurring after major earthquakes. Although a tsunami occurred in the Great Kanto Earthquake of 1923, it is believed to have had a wave height approximately half that of the tsunami in the Genroku Earthquake. However, this tsunami destroyed the livelihoods of villages and caused significant damage. In this study, we aim to reexamine historical records related to the tsunami in the Great Kanto Earthquake and objectively evaluate the actual situation of this tsunami disaster.